KLF feedback loops in innate immunity - Salmon, Jessica M.; Adams, Holly; Magor, Graham W.; Perkins, Andrew C. (Frontiers in Immunology, 2025)
The Krüppel-like factor (KLF) family of zinc finger transcription factors regulate the expression of genes involved in a wide range of cellular processes, including cell proliferation and differentiation. In haematopoiesis, KLFs have essential roles in myeloid cell differentiation and function. KLF4 is a critical regulator of macrophage development and initiates pro- and anti-inflammatory signalling pathways in response to various stimuli. KLF2, KLF3 and KLF6 also play important roles in regulating these pathways. Here we review how KLFs cooperate and compete to either activate or repress target genes to influence initiation and resolution of inflammatory responses in macrophages. We also discuss how KLFs may be involved in the development of chronic inflammatory conditions.